Pestiviral infection of llamas and alpacas - Evermann, J.F. (Small ruminant research, 2006)
This review summarizes the literature pertaining to pestiviral infections of members of the camelid family. The exact nature of pestiviral infections, in particular bovine viral diarrhea virus (BVDV), is the subject of active investigation especially in llamas and alpacas. Earlier reports based on serology-detected pestiviral (BVDV) antibodies in members of the camelid group ranging from a low 4% to a high of 53%. These studies indicate that members of the camelid group are susceptible to infection and do seroconvert. Over the past decade, clinical reports have documented disease conditions in llamas, alpacas and more recently, camels. These conditions range from respiratory and enteric diseases to chronic wasting and in utero infections resulting in stillbirths, and abortion. The review brings together some thoughts on whether infections of the camelid group are due to interspecies transmission and/or the potential that members of this group have their own unique pestiviral infections.